Differences in Attainment and Performance in a Foreign Language: The Role of Working Memory Capacity - Gilabert, Roger; Muñoz, Carmen (International Journal of English Studies, 2010)
The goal of this study is to investigate the role of working memory capacity in L2 attainment and performance. The study uses an L1 reading span task to measure working memory of a group of 59 high- intermediate/advanced learners of English, and a film retelling task to measure their oral production. The analysis first showed a moderate to high correlation between proficiency measured by a general proficiency test and learners’ fluency, lexical complexity, and accuracy but not structural complexity on the retelling task. Secondly, no correlation was found between overall proficiency and working memory. Thirdly, a weak correlation was found between fluency and lexical complexity, and working memory. When the group was split into top and bottom levels of proficiency, moderate correlations were found between lexical complexity and working memory only for the high-proficiency group. The results are discussed in the light of previous research.